2017
DOI: 10.1063/1.4981231
|View full text |Cite
|
Sign up to set email alerts
|

Sausage instabilities on top of kinking lengthening current-carrying magnetic flux tubes

Abstract: We theoretically explore the possibility of sausage instabilities developing on top of a kink instability in lengthening current-carrying magnetic flux tubes. Observations indicate that the dynamics of magnetic flux tubes in our cosmos and terrestrial experiments can involve topological changes faster than time scales predicted by resistive magnetohydrodynamics. Recent laboratory experiments suggest that hierarchies of instabilities, such as kink and Rayleigh-Taylor, could be responsible for initiating fast to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…https://doi.org/10.1017/S002237781800079X Downloaded from https://www.cambridge.org/core. IP address: 44.224.250.200, on 11 Aug 2020 at 10:11:33, subject to the Cambridge Core terms of use, available at fields shows that the kink is destabilized before the sausage; see von der Linden & You (2017).…”
Section: Kink Instabilitymentioning
confidence: 98%
See 2 more Smart Citations
“…https://doi.org/10.1017/S002237781800079X Downloaded from https://www.cambridge.org/core. IP address: 44.224.250.200, on 11 Aug 2020 at 10:11:33, subject to the Cambridge Core terms of use, available at fields shows that the kink is destabilized before the sausage; see von der Linden & You (2017).…”
Section: Kink Instabilitymentioning
confidence: 98%
“…Copyright 2009 by the American Physical Society.] fields shows that the kink is destabilized before the sausage; see von der Linden & You (2017).…”
Section: Kink Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a computational study on current-driven instabilities that used a 3D particle-incell code predicted the possibility of a sausage-to-kink cascade in the context of high energy particle production by a dense plasma focus [17]. Similarly, a recent analytic study by Von der Linden and You [18] suggested a current-driven instability cascade but in an opposite path, i.e., as a kink-to-sausage cascade. These studies suggest that if an MHD cascade results in progressively ner scales, the ion inertia scale and its associated fast non-MHD reconnection might be accessed.…”
mentioning
confidence: 99%
“…Studies suggest that there may also be minimum energy states subject to the conservation of fluid helicity [7] and canonical helicity [8][9][10][11], the weighted sum of helicities of magnetic and flow vorticity flux tubes. The dynamics of these relaxation processes can develop microscales, e.g., when flux tubes undergo instability cascades [12][13][14]. At these microscales, ion inertia, kinetic distribution functions, and finite Larmor radius effects become important, allowing ions and electrons to separate from the magnetic flux, which limits the usefulness of magnetic flux tubes for understanding relaxation dynamics.…”
mentioning
confidence: 99%